European Model of Private Security - Davidović, Dušan (Zbornik Instituta za kriminološka i sociološka istraživanja, 2014)
The development of the private security industry in Western Europe in the last two decades is marked mostly by serious efforts towards lifting the quality of security services, quality of working conditions and standardising both existing and new security demands and needs, produced by the modern way of living. Those efforts are operationalised in a concept well known as the European model of Private Security, which is thoroughly analysed in this article, both through its challenges and principles.